Legal Protection of Stateless Persons Arising From CrossBorder Marriage: Indonesia and East Timor Case Study - Nanik Trihastuti; Tri Laksmi Indreswari; Daniel René Kandou; Mira Novana Ardani; Diastama Anggita Ramadhan (Faculty of Law, Universitas Sebelas Maret, 2022)
Statelessness is a continuing international legal issue, with individuals lacking the protection of fundamental rights within the jurisdiction of a State. One aspect contributing to this problem is customary cross-border marriage between people of different nationalities, particularly in local border towns, for a variety of reasons. This study examines the phenomenon as a cause of statelessness and undocumented individuals and what the legal protection that international human rights instruments provide for States to comply. This study uses legal research by comparing the East Timor Constitution. Based on the study's results, the potential for statelessness and undocumented people due to cross-border marriage by custom has a detrimental effect on both women and children since it is difficult for them to obtain residence documents. Cross-border marriages between East Timorese men and Indonesian women by customary causing unregistered in Indonesia and East Timor. Field research shows that Indonesian women/wives in East Timor cannot exercise their rights since they are not East Timorese nationals. Noting the conflict of nationality laws between States, especially bordering States, the failure of both States to accommodate women that married are non-nationals breaches Article 9 of CEDAW and constitutes as discrimination against women defined under Article 1 of CEDAW